Analysis of Metal Contents in Portland Type V and MTA-Based Cements - Maura Cristiane Gonçales Orçati Dorileo; Matheus Coelho Bandeca; Fábio Luis Miranda Pedro; Luiz Evaristo Ricci Volpato; Orlando Aguirre Guedes; Ricardo Dalla Villa; Mateus Rodrigues Tonetto; Alvaro Henrique Borges (The Scientific World Journal)
The aim of this study was to determine, by Atomic Absorption Spectrometry (AAS), the concentration levels of 11 metals in Type V gray and structural white PC, ProRoot MTA, and MTA Bio. Samples, containing one gram of each tested cement, were prepared and transferred to a 100 mL Teflon tube with a mixture of 7.0 mL of nitric acid and 21 mL of hydrochloric acid. After the reaction, the mixture was filtered and then volumed to 50 mL of distilled water. For each metal, specific patterns were determined from universal standards. Arsenic quantification was performed by hydride generator. The analysis was performed five times and the data were statistically analyzed at 5% level of significance. Only the cadmium presented concentration levels of values lower than the quantification limit of the device. The AAS analysis showed increased levels of calcium, nickel, and zinc in structural white PC. Type V PC presented the greatest concentration levels of arsenic, chromium, copper, iron, lead, and manganese (P<0.05). Bismuth was found in all cements, and the lowest concentration levels were observed in Portland cements, while the highest were observed in ProRoot MTA. Both PC and MTA-based cements showed evidence of metals inclusion.